Inhibition of LDL-oxidation and antioxidant properties related to polyphenol content of hydrophilic fractions from seaweed Halimeda Incrassata (Ellis) Lamouroux (Brazilian Journal of Pharmaceutical Sciences, 2012)
LDL oxidation and oxidative stress are closely related to atherosclerosis. Therefore, natural antioxidants have been studied as promising candidates. In the present study, the LDL oxidation inhibition activity of bioactive compounds from Halimeda incrassata seaweed. associated to antioxidant capacity, was evaluated in vitro. Experimental work was conducted with lyophilized aqueous extract and phenolic-rich fractions of the seaweed and their effect on LDL oxidation was evaluated using heparin-precipitated LDL (hep-LDL) with exposure to Cu2+ ions and AAPH as the free radical generator. H. incrassata had a protective effect for hep-LDL in both systems and the presence of phenolic compounds contributed to the activity where phenolic-rich fractions showed significant capacity for inhibition of oxidation mediated by Cu2+ ions. The observed effect could be related to the antioxidant potential of polar fractions evidenced by reducing activity and DPPH radical scavenging. The results obtained in vitro further support the antioxidant and LDL oxidation inhibition properties of H. incrassata and further knowledge toward future phytotherapeutic application of the seaweed.